Mei Nu Examining Chinese Women's Deployment of Beauty in Four Biographical Texts - Carreon, Latasha Q.; Santamaria, Matthew Constancio M. (Asian Center, University of the Philippines Diliman, 2023)
Building on Bourdieu's notions of cultural capital, this qualitative research project aims to analyze four biographical texts of Chinese women--Gong Li, Zhang Ziyi, Fan Bingbing, and Hao Lulu--to characterize how they deploy their beauty as cultural capital, reflecting their agency and power vis-à-vis the structure (i.e. norms, class, institutions, and networks) of contemporary Chinese politics and society, particularly its beauty economy. Additionally, the research illustrates how beauty is constructed in contemporary China, tracing its historical antecedents to bring light to how beauty is entangled in politics, social norms, or economic concerns.

The analysis also reveals that the deployment of beauty as cultural capital serves the following objectives, such as career advancement; promotion of China's image; driving the beauty economy; and lending support for the government's programs. The case studies highlight both the agency of the four women as they deploy their beauty, while illustrating that such deployment is also shaped, even limited by state power, education, cultural norms, and the mass media. --Provided by the author.
Thesis (Master of Arts in Asian Studies) -- University of the Philippines Diliman
Keywords: Beauty culture -- China; Beauty, Personal -- China; Women -- China -- Social conditions; Sex role -- China